Bilateral nevus of Ota associated with Turner syndrome. - Alsaif, F.; Alshahwan, H. (European Journal of Pediatric Dermatology, 2010)
Here is reported a case of bilateral nevus of Ota in a 10-year-old girl with Turner syndrome and growth hormone deficiency. The cutaneous lesions got visible at the age of 6 months. In the following five years the skin lesions got more evident and widespread. They also darkened during the administration of the growth hormone. The ophthalmological examination showed, besides the conjunctival and scleral pigmentation, esotropia and nystagmus. The histological examination showed the presence of dermal melanocytes, confirming the clinical diagnosis of nevus of Ota. The cutaneous lesions were treated with Q-switched alexandrite laser. According to the Authors, this is the first case of nevus of Ota associated with Turner syndrome reported in the literature.